Intuitive Content Management System - Hoong, Chan Chung; M. A., Ameedeen (IEEE, 2015)
Content Management System (CMS) is a system that is used to control or manage content on a website such as text, links, image, HTML documents and other form of media. The aim of CMS is to help non-technical users to design their website. Resources hungriness is a critical problem in most of the CMS. A lot of development and software maintenance fees has been charged towards the society. Traditional CMS is not the best choice for the users who want to develop an easy and simple website because it is very heavy loaded and will indirectly decrease the website performance. The objective of this research is to develop an Intuitive Content Management System (ICMS) for non-technical users by using data-driven technology for creating a standard and user-friendly website easily. Users just need to choose the contents from a templates, upload images and fill up the necessary documents in order to create a quick, easy and dynamic website.